The meaning of Koto in Kono Oto Tomare’s Anime Movie: Roland Barthes Semiotic Approach - Theokarizia Sagitha Eka Devi; Tri Mulyani Wahyuningsih (International Forum of Researchers and Lecturers, 2023)
This research titled ‘The meaning of Koto in Kono Oto Tomare’s anime movie’. This movie is an adaption from manga Kono Oto Tomare! writen by Amyuu. This movie tells about the struggles of Tokise’s high school student which joined in Tokise’s Koto Club to defended their club from disbanded by vice principal. Method which used in this research is descriptive-qualitative method. For data analysis used Roland Barthes Semiotic theory. Roland Barthes Semiotic has two step of signification, first step has denotation, and then developed it into the second step that is connotation or myths.